Larsson/Magdalenić: Sociology in Sweden - Therborn, Göran (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
Book review of: Larsson, Anna, and Sanja Magdalenić (2015) Sociology in Sweden: A History, Basingstoke: Palgrave Macmillan. 105 pp. ISBN: 978-1-137-48229-7. Price: $ 67,50 (Hardcover)